Environmental Effects on Flutter Characteristics of Laminated Composite Rectangular and Skew Panels - T.V.R. Chowdary; P.K. Sinha; S. Parthan (Shock and Vibration)
A finite element method is presented for predicting the flutter response of laminated composite panels subjected to moisture concentration and temperature. The analysis accounts for material properties at elevated temperature and moisture concentration. The analysis is based on the first-order approximation to the linear piston theory and laminated plate theory that includes shear deformation. Both rectangular and skew panels are considered. Stability boundaries at moisture concentrations and temperatures for various lamination schemes and boundary conditions are discussed.